BRI as cognitive empire: Epistemic violence, ethnonationalism and alternative imaginaries in Zomian highlands. Issue 3 (31st March 2022) - Sims, Kearrin
Abstract : China's Belt and Road Initiative (BRI) has become the lodestar of Beijing's efforts to increase its global political and economic influence. This article interrogates BRI discourse, arguing that the normative adoption of BRI narratives as a means for making sense of connectivities between China and other places risks producing new forms of epistemic violence against subaltern populations. The empirical focus of this paper is on China‐Laos relations, and the epistemic positioning of highland ethnic minority groups in northern Laos. This context offers a valuable case study for examining BRI discourse due to: (a) the profound effects of Chinese investment in Laos; (b) the geostrategic importance of Laos as a BRI 'gateway' between China and Southeast Asia; (c) the deep histories of ethnic minority engagements across China and Laos; and (d) the limited extant research on both China‐Laos relations and the more localized effects of Chinese actors within the highland border regions.